Individualization and the Ideal of Self-Realization in Conditions of Reflexive Modernity - Turcan, Ciprian (Communications - Scientific letters of the University of Zilina, 2018)
Individualization as a modernization social phenomenon is of a highly ambivalent character. On the one hand, it represents the emancipation of individuals from general pressures of the society, from the traditional relations of domination and material dependence, the reduction of social pressure on the reproduction of traditional, typified social roles and lifestyles associated with social status and gender. On the other hand, individualization leads, under the current conditions, to increasing isolation of individuals in the context of instrumentalized, anonymous and fragmentary social relations and contacts, ultimately to forms of social deprivation. Emancipation creates room for an individual and subjectively gripped biography, for individual subjectively answering the question of good life, which promotes the ideal of individual self-realization as a new ideal of behavior and good life. However, the parallel process of social isolation seriously restricts and distorts the possibilities of its application. Based on this contradiction, this paper focuses on the critical exploration of the ways and forms of applying the ideal of self-fulfillment in contemporary society.